1994
DOI: 10.2466/pr0.1994.75.3.1369
|View full text |Cite
|
Sign up to set email alerts
|

Note on Assessing a Mentor Program

Abstract: To clarify the literature on mentor programs, self-esteem and grade point average after such a program were assessed for 30 boys and 46 girls in Grade 11 from 2 high schools. Mixed findings were discussed in terms of possible influences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…This line of research has resulted in conflicting findings regarding the effectiveness of formal mentoring programs (e.g., Granger, 1995;Roberts & Cotton, 1994;Thile & Matt, 1995). Thus, the purpose of this study was to understand how the mentoring process facilitates the personal and social adaptation of Latino students to college through an evaluation of a university FMP.…”
mentioning
confidence: 95%
“…This line of research has resulted in conflicting findings regarding the effectiveness of formal mentoring programs (e.g., Granger, 1995;Roberts & Cotton, 1994;Thile & Matt, 1995). Thus, the purpose of this study was to understand how the mentoring process facilitates the personal and social adaptation of Latino students to college through an evaluation of a university FMP.…”
mentioning
confidence: 95%
“…17 While there has been a proliferation of mentorship programs in recent years, particularly in school settings, there is a paucity of data evaluating these programs. 18 One of the problems with these evaluations is that the mentorship program may be a component of a larger intervention program to help at-risk adolescents, making it difficult to isolate the effect of mentorship alone. Also, it is often likely that the mentor may be involved in more than one program, making it difficult, when analyzing the data, to isolate the effect of the mentor from confounding factors.…”
Section: Commentmentioning
confidence: 99%
“…The authors found no significant changes between the mentorship group and controls; however, this may be because they were assessed after only 3 months. 18 Three months may be an insufficient interval for bonding, trust, and connectiveness to emerge. In another study of 36 at-risk African American youth who were matched with mentors, 21 it was found that there were no significant differences between the mentored group and controls with regard to self-esteem, attitudes about drugs and alcohol, grade point average, school absences, and disciplinary infractions.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In community programs, mentoring generally has been delivered through demographically matched adults (Blechman, 1992). Generally, mentoring has been shown to improve social functioning and skills acquisition among adolescents, although only when conducted over an extended duration of time and with a high quality of relationship (Frecknall & Luks, 1992;Rajala, Townsend & Taylor, 1996;Roberts & Cotton, 1994;Rogers & Taylor, 1997;Royse, 1998;Slicker & Palmer, 1993).…”
mentioning
confidence: 97%